Crafting a Faith-Based Intervention for Youth With ASD: Bar Mitzvah and Beyond. (1st October 2016) - Muskat, Barbara; Putterman, Connie
ABSTRACT: This article provides an overview of the conceptualization, development, delivery, and impact of a bar mitzvah preparation program led by parents of a child with autism spectrum disorder (ASD) in cooperation with congregational leadership, educators, and ASD researchers and practitioners. The unique aspects of the program were that it addressed the strengths, traits, and specialized needs of a group of preteen boys with ASD, in relation to the meaning, rituals, and tasks involved in a bar mitzvah. Its success relied heavily on the resources, energy, and persistence of parents.